Development of Student Worksheets for Economics Subjects Based on Learning by Doing - Suratno, Suratno (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2024)
This research aims to develop student worksheets based on Learning by Doing in learning Economics subjects for class X students at Senior High School 5 Jambi City. The development method used is Research and Development (R&D) by following the development model that has been agreed upon in the research process. The development stages include needs analysis, planning, product development, limited trials, revisions, field trials and evaluation. The research results showed that the Learning by Doing-based worksheets that were developed received positive responses from teachers and students. These worksheets can increase students' interest in learning and help them understand economic concepts better. Apart from that, these worksheets can also facilitate interactive, collaborative and applied learning in the classroom. Evaluation of the student worksheets shows that this product is suitable for use in learning Economics subjects at Senior High School 5 Jambi City. In conclusion, the development of Learning by Doing-based worksheets for Economics subjects can be an effective alternative in improving the quality of learning for class X students at Senior High School 5 Jambi City. It is hoped that the results of this research can make a positive contribution to the development of education in Indonesia, especially in the context of learning Economics subjects.